Ceramics Praises the Psalms.”The Holy Trinity” Church from Siret - Mihaela Simionescu (Anastasis: Research in Medieval Culture and Art, 2015)
”The Holy Trinity” (”Sfânta Treime”) church from Siret by tradition, should be the oldest monument in the form a clover of the religious architecture of Moldavia. By its architectural and decorative elements, the exterior of this church entirely foreshadows the artistic virtues of monuments from the time of Petru I Muşat. Therefore, the apses have a series of niches elongated at their edges with semicircular arches and decorated in tambourines with bricks. Values are plan and decoration items speaking about relations with the Byzantine-Balkan world. The outside consisting of rough gray-green stone of the monument is refreshed by a bright and harmonious scenery of ceramic ornaments made out of bricks, leg discs in the form of mushrooms and cruciform colored flowers. At the top of the monument, about two thirds of the height of the walls (from the pedestal upwards), there can be seen a frieze consisting of two rows of discs alternating with cruciform flowers. They range from the apses (the south side as well) all the way up to the window of the narthex. The semicircular arches of brick niches are also sharpened by a row of discs alternating with cruciform flowers. The windows with the exception of the one of the northern apse are decorated at the top with one rectangular frame consisting of two rows of glazed discs and three cruciform flowers, all framed by glazed bricks (either plain or coloured). The same decoration can also be seen at the niche above the entrance door destined for the church icon. Above this frame, there can be seen a cornice made out of bricks arranged in a zig zag pattern. The continuous development and enrichment of the ceramic façade during the next century will lead to the finishing touches, in the reign of Stefan cel Mare (Stephen the Great), of a harmonious and original decorative.